THE CONSTRUCTION OF THIRD SPACE IN ELIF SHAFAK’S TWO NOVELS - Asyifa, Nurul Hanun; Zulyeno, Bastian (UI Scholars Hub, 2023)
This article analyzes how public spaces—in the forms of two cafes and a tavern—are constructed as a third space in Elif Shafak's two novels, “The Bastard of Istanbul” (2008) and “The Island of Missing Trees” (2021). This research is a qualitative study with an approach in spatiality. The theory used in this study is the theory of Thirdspace by Edward Soja. The results of the study indicate that as the representation of the third space, the two cafes and a tavern in Shafak's two novels promote resistance to the conflicts and their impacts on the two conflicting groups, as well as constructed as sites that unite the groups. In “The Bastard of Istanbul”, the communication and relationships between the characters in Café Kundera and Café Constantinopolis show resistance to issues related to the 1915 Armenian genocide that gives impacts on the Turkish and Armenian relationship. Moreover, in “The Island of Missing Trees”, the characters’ friendship and intimacy at The Happy Fig Tavern show opposition to the ongoing internal conflict between Greek Cypriots and Turkish Cypriots which causes ethnic and territorial separation. A further examination of the third space reveals two different ways in how Shafak presents public spaces in both novels, specifically in terms of the visitors’ portrayal and the two distinct eras in which these public spaces are set. The outcomes of these two differences show that: (1)